Computer‐assisted cognitive behavioural therapy: The experiences of adults who have an intellectual disability and anxiety or depression. Issue 6 (3rd May 2018) - Cooney, Patricia; Jackman, Catherine; Tunney, Conall; Coyle, David; O'Reilly, Gary
Abstract : Background: Despite its evidence base in the general population, computerized cognitive behavioural therapy (cCBT) has not yet been adapted for use with people with intellectual disability. This study aimed to explore the experiences of adults with an intellectual disability who played a cCBT program. Method: Twenty‐four adults (with a mild or moderate intellectual disability and clinically significant anxiety or depression) who were in the treatment arm of a pilot randomized controlled trial evaluating the cCBT program were individually interviewed. Thematic analysis was used to analyse and report themes within the data. Results: Participants found playing the program to be an enjoyable and novel experience and that it was challenging and helpful. It allowed them to develop and reflect on relationships and increased their awareness of thoughts, feelings and behaviours. Conclusions: Combining technology with CBT is an effective way to reduce barriers to accessing mental health interventions and technology for this population.